“Iron-coated Seed” Technology - a Strategy for Improving Seedling Establishment in Direct Seeded Rice - Kumar, K. Ashok; Reddy, B. Sahadeva (Chronicle of Bioresource Management, 2021)
In recent years, there has been a considerable shift from transplanted method to direct seeded rice cultivation in several rice growing countries. This trend is principally driven by water scarcity issues, expensive farm labour for transplantation and acute shortage of labour. Despite many advantages with direct seeded rice, certain problems associated with this method like inconsistent seedling establishment and heavy weed infestation need attention. This paper focuses on the strategy for improving seedling establishment through “Iron-coated seed” technology. In this method, pre-germinated seeds are granulated with a mixture of reduced Fe powder and calcined gypsum. The iron-coated seeds are prepared through the oxidation of reduced Fe on seed surface forming rust, which serves as a binder for the formation of a hard coating layer. The high density iron-coated seeds are resistant to bird damage, low/no floatation, minimize seed-borne diseases and efficiently improve anchorage in water/wet seeding in puddled fields.